Application of Self-Care Behaviour Scale for Arterio Venous Fistula Among Hemodialysis Patients - Ihab Nadhir Ghazi, Widad Kamil Mohammed (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To evaluate self-care behavior for Arterio Venous Fistula among Hemodialysis Patients Methods: Descriptive research was carried out using a scale to assess the self-care habits of dialysis patients with CKD. The study was conducted on (5) teaching hospitals in Baghdad City from the Artificial Kidney Centers divided into three Health Directorate: Results: Result show that the highest evaluation rate for Item(No.3) I do compression of puncture sites with the fingers (hemostasis). in the rate of RS%(70.72)rated fair self-care behaviors" While the lowest evaluation rate for item No. 25 (I shave the hairs on the fistula arm( in the rate of RS% (31.44)rated Poor self-care behavior. Majority of patients in this study experienced with a fair level of knowledge regarding self-care behaviors of AV fistula 425 (85.0%). Conclusions: Majority of patients in this study experienced with a fair level of knowledge regarding self-care behaviors of AV fistula.